Designing Structural Electrochemical Energy Storage Systems: A Perspective on the Role of Device Chemistry - Navarro-Suárez, Adriana M.; Shaffer, Milo S. P. (Frontiers in Chemistry, 2022)
Structural energy storage devices (SESDs), designed to simultaneously store electrical energy and withstand mechanical loads, offer great potential to reduce the overall system weight in applications such as automotive, aircraft, spacecraft, marine and sports equipment. The greatest improvements will come from systems that implement true multifunctional materials as fully as possible. The realization of electrochemical SESDs therefore requires the identification and development of suitable multifunctional structural electrodes, separators, and electrolytes. Different strategies are available depending on the class of electrochemical energy storage device and the specific chemistries selected. Here, we review existing attempts to build SESDs around carbon fiber composite electrodes, including the use of both organic and inorganic compounds to increase electrochemical performance. We consider some of the key challenges and discuss the implications for the selection of device chemistries.